Choroidal neovascularisation following inverted internal limiting membrane flap technique for idiopathic macular hole: a case for modified flaps. Issue 1 (18th January 2021) - Gupta, Nikita; Mehta, Aditi; Dogra, Mohit; Singh, Simar Rajan
Abstract : A 70-year-old woman presented with sudden decrease of vision 2 months following a successful vitrectomy with inverted internal limiting membrane flap for a full thickness macular hole. Serial review of fundus pictures and optical coherence tomography scans revealed a focal retinal pigment epithelial disruption at the site of the macular hole after surgery and a choroidal neovascular membrane arising from the same. This report describes the possible role of the surgical technique in causation of the membrane and discusses modifications to avoid the same.